Prognostic significance of SOX2, SOX3, SOX11, SOX14 and SOX18 gene expression in adult de novo acute myeloid leukemia. (April 2018) - Tosic, Natasa; Petrovic, Isidora; Grujicic, Natasa Kovacevic; Davidovic, Slobodan; Virijevic, Marijana; Vukovic, Nada Suvajdzic; Pavlovic, Sonja; Stevanovic, Milena
Highlights: SOX2, SOX3, SOX11, SOX14 and SOX18 genes are overexpressed in 10–22% AML patients. SOX high status is associated with the presence of FLT3 and NPM1 mutations. SOX high patients have shorter disease-free and overall survival. Abstract: Aberrant expression of different SOX (SRY-related high mobility group (HMG) box) genes has been observed in number of tumors but, little is known about their expression patterns in hematological malignancies, especially in acute myeloid leukemia (AML). In this study we investigated SOX2, SOX3, SOX11, SOX14 and SOX18 gene expression in 50 de novo adult AML patients and correlated our findings with known clinical and molecular prognostic markers of the disease. We have found that these genes are overexpressed in 10–22% of patients and preliminary findings suggest that high expression level of these genes may have prognostic significance in AML patients. This is the first study focused on examining the expression level of SOX2, SOX3, SOX11, SOX14 and SOX18 genes in AML patients. Although this is a relatively limited study, initial findings indicate the need for further investigation of these genes, their potential roles in leukemia pathogenesis as well as prognosis in AML patients.